The Impact of Agricultural Land Conversion into Residential Areas on Landslide Incidents in Belik Village, Trawas District, Mojokerto Regency - Ratnawati, Rhenny; Shofwan, Moch.; Mukhtar, M. Nushron Ali; Majid, Dian; Nugroho, Arif Rahman (Jurnal Geografika (Geografi Lingkungan Lahan Basah), 2024)
The conversion of agricultural land into residential areas in Desa Belik, Kecamatan Trawas, Kabupaten Mojokerto, has significantly increased the risk of landslides. This research aims to examine the impact of land conversion on landslide incidents using secondary data regarding supporting variables related to the potential threat of landslides and the landscape of the area. This research uses a descriptive qualitative approach. The research results show that the conversion of agricultural land into residential areas increases both physical and non-physical vulnerability to potential landslides. The research results show that conversion of agricultural land into residential areas increases vulnerability to landslides. The conclusion is that implementing stricter disaster mitigation policies and implementing excellent spatial planning that prioritizes ecological sustainability is crucial in reducing the potential risk of landslides in the future.